New algorithms for identifying the flavour of B0 mesons using pions and protons. - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Cazon, BR; Hadavizadeh, T; Harnew, N; Hill, DRF; Jalocha, PG; John, MJJ; Malde, S; et al. (Springer, 2017)
Two new algorithms for use in the analysis of pp collision are developed to identify the flavour of B0 mesons at production using pions and protons from the hadronization process. The algorithms are optimized and calibrated on data, using B0→ D−π+ decays from pp collision data collected by LHCb at centre-of-mass energies of 7 and 8TeV. The tagging power of the new pion algorithm is 60% greater than the previously available one; the algorithm using protons to identify the flavour of a B0 meson is the first of its kind..